Sosialisasi Pembuatan Biopori Untuk Menanggulangi Banjir Dan Genangan Di Desa Kutamukti - Suryadinatha Dwi Afrilian Sarmudin; Vita Aprilina; Yuha Nadhirah Qintharah (Kreativasi : Journal of Community Empowerment, 2022)
Floods are one of the disasters that still often occur in various regions in Indonesia, floods occur because of high rainfall that is not accompanied by green open spaces and clean river flows from garbage, therefore the plan for the biopore program is intended to minimize the occurrence of puddles. and flooding because water from the soil surface flows directly into the biopori media so that the water does not stay long on the soil surface, Biopori aims to improve the quality of groundwater and nutrients in the soil because the biopori media is filled with organic materials such as vegetable waste and leaves. fall / dry so that it is expected to be able to minimize air pollution from burning garbage because it is not uncommon for people who still burn garbage and waste in their yards, therefore the author makes a program with socialization and training methods so that people want to implement a biopore system around their yards to minimize flood control and puddles as well as organic waste in the biopore media can be used as compost. Overall, the community service activities that have been carried out are going well. Participation, cooperation, and assistance from the parties involved, both internally and externally, were carried out well. The results of the implementation of this community service activity are compiled with and adjusted to the stages of implementing the activities that have been carried out.